PERUBAHAN KUALITAS TANAH SAWAH DI AREAL SEKITAR PENAMBANGAN BATUBARA DI KABUPATEN BANJAR - Irfan Syarif; Bambang Joko Priatmadi; Eko Rini Indrayatie; Abdul Haris (EnviroScienteae, 2011)
This study aimed to determine of soil quality changes in paddy fields contaminated by coal waste. Descriptive research was conducted at the Mangkaok village, Kecamatan Pengaron, Kabupaten Banjar, South Kalimantan. Paddy fields contaminated by coal waste (LK) and the paddy fields isn’t contaminated (LtK) became study location. Soil quality indicators have been analized in the Environmental Research Center Laboratory, Lambung Mangkurat University, Banjarbaru were bulk density of soil, C-organic, cation exchange capasity (CEC), totally of N soil, P-available, K-exchangeable, soil pH, Fe-soluble, Mn-soluble, SO42-, and soil texture. Water quality of the source impacts were analyzed as supporting data. This study was conducted from March to June 2010.  This study results showed bulk density of soil, soil pH, and K-exchangeable between LtK and LK have significant differences, whereas C-organic, totally of N soil, P-available, CEC, Fe-soluble, Mn-soluble, SO42-, and clay content didn’t significant differences. Bulk density of LK is heavier than LtK, potassium exchangeable of LK is higher than LtK and soil pH of LK is lower than Ltk.